Pembuatan Sistem Multiuser Untuk Persediaan Barang Dengan Metode Last In First Out - Rini Rubhiyanti; Uswatun Khasanah; Febryantahanuji Febryantahanuji (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Business processes that are carried out still use manual recording where purchase transactions, inventory recording, and sales records are recorded in the book. Manual recording was deemed less effective and efficient and also resulted in a more complicated inventory reporting process. The purpose of this study is to develop an inventory information system using the Last In First Out (LIFO) method where the unit sold is the last unit entered, making it easier to organize goods, both entering and retrieving goods, and goods will sell quickly because they follow the trend with the latest models that generate more profit. large and this system is also equipped with a minimum stock limit report aimed at knowing the minimum stock limit of goods so that it can provide up to date notifications about out of stock items. By implementing this system, it is hoped that users will find it easier to carry out their business processes.